Women’s mood at high altitude. sexual dimorphism in hypoxic stress modulation by the tryptophan–melatonin axis - Alcantara-Zapata, D. E.; Lucero, N.; De Gregorio, N.; Astudillo Cornejo, P.; Ibarra Villanueva, C.; Baltodano-Calle, M. J.; Gonzales, G. F.; Behn, C. (Frontiers in Physiology, 2023)
Sex (and gender) dimorphism in tolerance to hypobaric hypoxia increasingly matters for a differentiated surveillance of human activities at high altitude (HA). Prevalence of anxiety and depression in women already doubling that of men at low altitude can be expected to even increase on exposure to HA. Purposefully caring for health of women at HA, the present work explores a potential involvement of the tryptophan-melatonin axis in mood changes on exposure to hypobaric hypoxia. The present work highlights some already known anxiogenic effects of HA exposure. Hypoxia and insomnia may be involved by reducing serotonin (5-HT) availability, the latter defect expressing in failure of brown adipose tissue activation and finally in mood disorders. REM sleep organization and synapsis restoration affected by hypoxia impair consolidation of memory, including the emotional one. Affective complaints, thus, may surge, evolving into anxiety and depression. Sex-related differences of neural network organization and hormonal changes along menstrual cycle, and certainly also along life cycle, moreover, underscore the possibility of 5-HT related mood alterations, particularly occurring in women on HA exposure. Mean brain rate of 5-HT synthesis at sea level is already 1.5-fold higher in males than in females. A related sex-dimorphism also evidences in overexpression effects of SERT, a 5-HT transporter protein. Other hormones further modulate 5-HT generation and effects in women. Besides caring for adequate oxygenation and maintenance of body core temperature, special precautions to consider for women sojourning at HA should include close observations of hormonal cycles and, perhaps, also trials with targeted antidepressants